Flexible aramid-based triboelectric nano electrode material with high elasticity and high stacking power density and preparation method of flexible aramid-based triboelectric nano electrode material

CN119159893AActive Publication Date: 2024-12-20WUHAN TEXTILE UNIV +1
View PDF -1 Cites 0 Cited by

Patent Information

Application Number
CN202411229010.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-20
Estimated Expiration
2044-09-03

AI Technical Summary

Technical Problem

Traditional underwater triboelectric nanogenerators have large volume and low output performance. In an underwater environment, the triboelectric effect is affected by water flow and pressure, making it difficult to achieve efficient energy collection.

Method used

Using flexible aramid-based friction electroelectric nanoelectrode material with high elasticity and high accumulation power density, the meta-aramid nanofiber membrane is prepared by electrospinning, and blended with conductive rubber latex to form a flexible electrode material with a multi-layer structure, which is enhanced. Material elasticity and triboelectric output performance.

Benefits of technology

It achieves high fracture strength, high elasticity and high friction electrical output, significantly improving the performance of underwater triboelectric nanogenerators, suitable for lightweight and efficient energy collection, reducing structural burden, and suitable for underwater environment applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119159893A_ABST
    Figure CN119159893A_ABST
Patent Text Reader

Abstract

The invention relates to a flexible aramid-based triboelectric nano electrode material with high elasticity and high stacking power density and a preparation method of the flexible aramid-based triboelectric nano electrode material. The flexible aramid-based triboelectric nano electrode material with high elasticity and high stacking power density is constructed by adopting electrostatic spinning and rubber in-situ infiltration. The preparation method comprises the following steps: carrying out electrostatic spinning on a meta-aramid solution, infiltrating the meta-aramid solution into a brominated butyl rubber / conductive carbon black solution containing ionic liquid with cationic groups, and carrying out an in-situ reaction to form the asymmetric flexible aramid-based triboelectric electrode material. And the underwater triboelectric nano generator with high stacking power density is further assembled. Due to the fact that the strong cation contained in the ionic liquid with the cationic group and pi electrons of the meta-aramid and the brominated butyl rubber / conductive carbon black respectively form a pi electron-strong cation strong interface effect, the elasticity and the frictional electricity output performance of the ionic liquid are remarkably improved. Meanwhile, based on the strength of the aramid fiber matrix, the constructed underwater triboelectric nano generator does not need external support, and the stacking power density is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of triboelectric nanoelectrode materials, and in particular to a flexible aramid-based triboelectric nanoelectrode material with high elasticity and high stacking power density and a preparation method thereof. Background Art

[0002] In 2012, the team of Academician Wang Zhonglin invented the friction nanogenerator for the first time, marking the beginning of a new field of energy harvesting and self-driven sensing. Based on the principles of contact electrification and electrostatic induction, the friction nanogenerator can efficiently collect the widely distributed and ubiquitous mechanical energy around people, providing a paradigm for self-driven systems, future energy technologies, and the utilization of high-entropy energy. Among them, underwater triboelectric nanogenerators, as an emerging energy harvesting technology, use the triboelectric effect to convert mechanical energy into electrical energy underwater, and have broad application prospects, such as underwater sensors, microelectronic devices, and marine energy harvesting. However, these generators face the challenges of large size and low output performance in practical applications. Traditional underwater triboelectric nanogenerators require a large volume to increase the friction surface area, thereby improving energy output, but this also brings about an increase in system complexity and manufacturing costs, such as Chinese patents CN117937881A and CN117738840A. In order to overcome these problems, researchers are exploring new design concepts, such as optimizing materials and improving structural design. In addition, the triboelectric effect in underwater environments is affected by water flow and pressure, which reduces the power generation capacity. Researchers are trying to improve the performance of triboelectric nanogenerators through nanotechnology and materials science, and develop more efficient materials and structural designs to solve the problems of large size and low performance.

[0003] Aramid is one of the chemical fibers with the highest mechanical strength made by humans. Therefore, choosing aramid as the substrate for unsupported underwater triboelectric nanogenerators is a good choice. However, aramid materials are too rigid to show excellent triboelectric output performance in the face of complex ocean current environments. Electrospun membranes prepared by electrospinning technology show higher triboelectric output than dense membranes. Among them, the simplicity of triboelectric nanogenerators can be more easily maintained by constructing electrode materials that are sensitive to micromechanical waves. Triboelectric materials with rigid substrates show stable shape retention and stable output, but their triboelectric output performance is relatively low under micromechanical impact. In contrast, soft elastic triboelectrodes based on advanced porous materials have been used to collect triboelectric energy from micromechanical impacts, while significantly reducing mechanical properties. Therefore, in the electrode materials of underwater triboelectric nanogenerators, balancing the output stability of the rigid substrate and the output performance of the soft substrate is a promising research direction.

[0004] Therefore, aramid-based electrode materials with high elasticity and high stacking power density are of great significance in the practical application of underwater triboelectric nanogenerators. The unique structure gives the material excellent strength and flexibility, which is suitable for manufacturing lightweight and high-efficiency materials, giving it the potential to efficiently collect energy underwater. This material not only helps to reduce structural burden and improve performance, but can also be used in wearables, engineering and other fields, showing a wide range of application potential. Summary of the invention

[0005] In view of the above problems, the object of the present invention is to provide a flexible aramid-based triboelectric nanoelectrode material with high elasticity and high stacking power density and a preparation method thereof.

[0006] The technical solution of the present invention to solve the above technical problems is as follows:

[0007] The method for preparing a flexible aramid-based triboelectric nanoelectrode material with high elasticity and high stacking power density specifically comprises the following steps:

[0008] Step 1, dissolving meta-aramid with an organic solvent to obtain a meta-aramid solution, and performing electrostatic spinning using the meta-aramid solution to obtain a meta-aramid nanofiber membrane;

[0009] Step 2, blending an ionic liquid with a cationic group, brominated butyl rubber and conductive carbon black to prepare a conductive rubber latex;

[0010] Step 3: stack multiple layers of meta-aramid and immerse them together in the conductive rubber latex obtained in the previous step, take them out and dry them at high temperature to obtain a flexible aramid-based triboelectric electrode material.

[0011] Furthermore, in step 1, lithium bromide and N,N-dimethylacetamide are used to dissolve meta-aramid, and the mass fractions of meta-aramid, lithium bromide and N,N-dimethylacetamide are 8%, 10% and 82% respectively, and the dissolution temperature is between 60 and 90°C.

[0012] Furthermore, during electrospinning, the positive voltage of the electrospinning machine is +18 kV, the negative voltage is -6 kV, the spinning speed is between 1 and 1.5 mL / h, the spinning temperature is greater than 15°C, the humidity is less than 50%, the spinning solution is not less than 5 mL, and the needle model is: 23G.

[0013] Furthermore, in step 3, the mass fractions of the cationic ionic liquid, brominated butyl rubber, conductive carbon black and tetrahydrofuran are 0.21%, 20.92%, 0.44% and 78.43% respectively.

[0014] Furthermore, the cation-carrying ionic liquid includes any one of butyl imidazole, 1-decyl-3-methyl imidazole tetrafluoroborate, 1-alkyl-2,3-dimethyl imidazole and 2-alkyl-methyl imidazole.

[0015] Furthermore, in step 3, the number of layers of the meta-aramid film is three, the size is 5 cm×5 cm, the content of the conductive rubber latex is 5 to 25 mL, and the oven temperature is between 110 and 120° C.

[0016] Flexible aramid-based triboelectric nanoelectrode material with high elasticity and high stacking power density is prepared by the above method.

[0017] The beneficial effects of the present invention are as follows: On the one hand, the present invention generates π-cation interactions between the aromatic benzene rings and the π electrons in the imidazole rings in the meta-aramid molecular chain and the imidazole cations of the ionic liquid with cationic groups. This interaction enhances the binding ability between butyl imidazole and the meta-aramid surface. On the other hand, the aromatic benzene rings of the conductive carbon black in the brominated butyl rubber / conductive carbon black interact with the imidazole rings of the ionic liquid to form a stable ionomer. Based on the strong interfacial interaction between the ionic liquid and the meta-aramid and the brominated butyl rubber / conductive carbon black, the interfacial compatibility of the aramid-based triboelectric electrode material formed by the brominated butyl rubber / conductive carbon black immersed in the meta-aramid electrospun membrane is improved, resulting in a significant improvement in its elasticity. In addition, the brominated butyl rubber / conductive carbon black forms an asymmetric gradient structure in the electrospun meta-aramid membrane (the pure meta-aramid on the surface serves as a triboelectric dielectric layer, while the meta-aramid / bromobutyl rubber / conductive carbon black in the lower layer serves as a conductive layer), resulting in a significant improvement in triboelectric output performance. The high fracture strength, high elasticity and high triboelectric output performance demonstrated by aramid-based underwater triboelectric nanogenerators play a vital role in underwater triboelectric nanogenerators without external support. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a schematic diagram of the method flow of the present invention;

[0019] Figure 2 Optical image of aramid-based triboelectric electrode;

[0020] Figure 3 Optical image of aramid-based triboelectric nanogenerator;

[0021] Figure 4 is the stretching curve of aramid-based triboelectric electrode;

[0022] Figure 5 Optical images of aramid-based triboelectric nanogenerators under various compression and rebound conditions;

[0023] Figure 6 is the output voltage of the underwater triboelectric nanogenerator of the aramid-based triboelectric nanogenerator. DETAILED DESCRIPTION

[0024] The principles and features of the present invention are described below in conjunction with specific embodiments. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0025] like Figure 1 As shown, the flexible aramid-based triboelectric nanoelectrode material with high elasticity and high stacking power density is:

[0026] Step 1, using lithium bromide and N,N-dimethylacetamide solvent to dissolve meta-aramid;

[0027] Step 2, forming a film by electrospinning the obtained meta-aramid solution;

[0028] Step 3, blending an ionic liquid with a cationic group, brominated butyl rubber and conductive carbon black to prepare a conductive rubber latex;

[0029] Step 4, soaking the multilayer meta-aramid in the conductive rubber latex and drying it at high temperature to obtain a flexible aramid-based triboelectric electrode material;

[0030] Step 5: Assemble the flexible aramid-based triboelectric electrode material with polyvinylidene fluoride, polyimide and other materials into an underwater triboelectric nanogenerator.

[0031] Specifically, in the step 1, the mass proportions of meta-aramid, lithium bromide and N,N-dimethylacetamide are 8%, 10% and 82%, respectively, and the dissolution temperature is between 60 and 90°C.

[0032] Specifically, in the step 2, the positive voltage of the electrospinning machine is +18kV, the negative voltage is -6kV, the spinning speed is between 1 and 1.5mL / h, the spinning temperature is greater than 15°C, the humidity is less than 50%, the spinning solution is not less than 5mL, and the needle model is: 23G.

[0033] Specifically, in the step three, the mass proportions of the ionic liquid with a cationic group, brominated butyl rubber, conductive carbon black and tetrahydrofuran are 0.21%, 20.92%, 0.44% and 78.43%, respectively, wherein the ionic liquid with a cationic group includes butyl imidazole, 1-decyl-3-methyl imidazole tetrafluoroborate, 1-alkyl-2,3-dimethyl imidazole and 2-alkyl-methyl imidazole, etc.

[0034] Specifically, in step 4, the number of layers of the meta-aramid film is fixed at three, the size is 5 cm×5 cm, the content of the conductive rubber latex is 5 to 25 mL, and the oven temperature is between 110 and 120° C.

[0035] Specifically, in step five, the materials used and their functions are polyvinylidene fluoride film (triboelectric negative electrode material), flexible copper tape (conductive layer), polyimide tape (packaging material), polyethylene film (packaging material) and wire, wherein after the electrode material and the conductive layer are encapsulated with polyimide tape, the polyethylene film is plastic-sealed by a heating plastic sealing machine.

[0036] like Figure 1 As shown, the method of the present invention includes the following aspects: using lithium bromide and N, N-dimethylacetamide solvents to dissolve meta-aramid; forming the obtained meta-aramid solution into a film by electrostatic spinning; preparing a conductive rubber latex by blending butyl imidazole, bromobutyl rubber and conductive carbon black; soaking multiple layers of meta-aramid in the conductive rubber latex, and drying at high temperature to obtain a flexible aramid-based triboelectric electrode material; assembling the flexible aramid-based triboelectric electrode material with polyvinylidene fluoride, polyimide and other materials into an underwater triboelectric nanogenerator;

[0037] like Figure 2 As shown, the aramid-based triboelectric electrode exhibits the characteristics of meta-aramid on the upper surface and meta-aramid / bromobutyl rubber / conductive carbon black composite on the lower surface;

[0038] like Figure 3 As shown, the aramid-based triboelectric nanogenerator exhibits the characteristics of small overall size;

[0039] like Figure 4 As shown, the elongation at break of the aramid-based triboelectric electrode exceeds 100%, and the breaking strength exceeds 50 mPa. It exhibits excellent mechanical strength and tensile strength;

[0040] like Figure 5 As shown, the aramid-based triboelectric nanogenerator exhibits excellent resilience against bending and twisting, showing potential for application in resisting water flow underwater.

[0041] like Figure 6 As shown, the maximum output voltage of the aramid-based triboelectric nanogenerator reaches 200V, and the higher the frequency of the water wave, the more triboelectric peaks there are and the higher the average voltage.

[0042] Embodiment 1:

[0043] A method for preparing an aramid-based underwater triboelectric nanogenerator with high elasticity and high stacking power density, the preparation method comprising:

[0044] Step 1: dissolve 5 g of meta-aramid at 80° C. using 4 g of lithium bromide and 41 g of N,N-dimethylacetamide solvent;

[0045] Step 2, electrospin 10 mL of meta-aramid solution into a film under the conditions of positive voltage +18 kV, negative voltage -6 kV, spinning speed 1 mL / h, spinning temperature 30°C, humidity 40%, and 23G needle;

[0046] Step 3, 0.21 g of butyl imidazole, 20.92 g of brominated butyl rubber and 0.44 g of conductive carbon black were mixed with 78.43 g of tetrahydrofuran to prepare a conductive rubber latex;

[0047] Step 4: soak three layers of meta-aramid (5 cm×5 cm) in 5, 10, 15, 20, and 25 mL of conductive rubber latex, and dry them at a high temperature of 110° C. to obtain a flexible aramid-based triboelectric electrode material;

[0048] Step 5: Assemble the flexible aramid-based triboelectric electrode with polyvinylidene fluoride film, flexible copper tape, polyimide tape, polyethylene film and wire into a triboelectric nanogenerator, and then use a heating plastic sealing machine to plastic seal the polyethylene film. This will yield an aramid-based underwater triboelectric nanogenerator with high elasticity and high stacking power density.

[0049] Embodiment 2:

[0050] A method for preparing an aramid-based underwater triboelectric nanogenerator with high elasticity and high stacking power density, the preparation method comprising:

[0051] Step 1: dissolving 5 g of meta-aramid at 80° C. using 4 g of lithium bromide and 41 g of N,N-dimethylacetamide solvent;

[0052] Step 2, electrospin 10 mL of meta-aramid solution into a film under the conditions of positive voltage +18 kV, negative voltage -6 kV, spinning speed 1 mL / h, spinning temperature 30°C, humidity 40%, and 23G needle;

[0053] Step 3, 0.21 g of 1-decyl-3-methylimidazolium tetrafluoroborate, 20.92 g of brominated butyl rubber and 0.44 g of conductive carbon black were mixed with 78.43 g of tetrahydrofuran to prepare a conductive rubber latex;

[0054] Step 4: soak three layers of meta-aramid (5 cm×5 cm) in 10 mL of conductive rubber latex and dry them at a high temperature of 110° C. to obtain a flexible aramid-based triboelectric electrode material;

[0055] Step 5: Assemble the flexible aramid-based triboelectric electrode with polyvinylidene fluoride film, flexible copper tape, polyimide tape, polyethylene film and wire into a triboelectric nanogenerator, and then use a heating plastic sealing machine to plastic seal the polyethylene film. This will yield an aramid-based underwater triboelectric nanogenerator with high elasticity and high stacking power density.

[0056] Embodiment three:

[0057] A method for preparing an aramid-based underwater triboelectric nanogenerator with high elasticity and high stacking power density, the preparation method comprising:

[0058] Step 1: dissolving 5 g of meta-aramid at 80° C. using 4 g of lithium bromide and 41 g of N,N-dimethylacetamide solvent;

[0059] Step 2, electrospin 10 mL of meta-aramid solution into a film under the conditions of positive voltage +18 kV, negative voltage -6 kV, spinning speed 1 mL / h, spinning temperature 30°C, humidity 40%, and 23G needle;

[0060] Step 3, 0.21 g of 1-decyl-3-methylimidazolium hexafluorophosphate, 20.92 g of brominated butyl rubber and 0.44 g of conductive carbon black were mixed with 78.43 g of tetrahydrofuran to prepare a conductive rubber latex;

[0061] Step 4: soak three layers of meta-aramid (5 cm×5 cm) in 10 mL of conductive rubber latex and dry them at a high temperature of 110° C. to obtain a flexible aramid-based triboelectric electrode material;

[0062] Step 5: Assemble the flexible aramid-based triboelectric electrode with polyvinylidene fluoride film, flexible copper tape, polyimide tape, polyethylene film and wire into a triboelectric nanogenerator, and then use a heating plastic sealing machine to plastic seal the polyethylene film. This will yield an aramid-based underwater triboelectric nanogenerator with high elasticity and high stacking power density.

[0063] Embodiment 4:

[0064] A method for preparing an aramid-based underwater triboelectric nanogenerator with high elasticity and high stacking power density, the preparation method comprising:

[0065] Step 1: dissolving 5 g of meta-aramid at 80° C. using 4 g of lithium bromide and 41 g of N,N-dimethylacetamide solvent;

[0066] Step 2, electrospin 10 mL of meta-aramid solution into a film under the conditions of positive voltage +18 kV, negative voltage -6 kV, spinning speed 1 mL / h, spinning temperature 30°C, humidity 40%, and 23G needle;

[0067] Step 3, 0.21 g of 1-alkyl-2,3-dimethylimidazole, 20.92 g of brominated butyl rubber and 0.44 g of conductive carbon black were mixed with 78.43 g of tetrahydrofuran to prepare a conductive rubber latex;

[0068] Step 4: soak three layers of meta-aramid (5 cm×5 cm) in 10 mL of conductive rubber latex and dry them at a high temperature of 110° C. to obtain a flexible aramid-based triboelectric electrode material;

[0069] Step 5: Assemble the flexible aramid-based triboelectric electrode with polyvinylidene fluoride film, flexible copper tape, polyimide tape, polyethylene film and wire into a triboelectric nanogenerator, and then use a heating plastic sealing machine to plastic seal the polyethylene film. This will yield an aramid-based underwater triboelectric nanogenerator with high elasticity and high stacking power density.

[0070] Embodiment 4:

[0071] A method for preparing an aramid-based underwater triboelectric nanogenerator with high elasticity and high stacking power density, the preparation method comprising:

[0072] Step 1: dissolving 5 g of meta-aramid at 80° C. using 4 g of lithium bromide and 41 g of N,N-dimethylacetamide solvent;

[0073] Step 2, electrospin 10 mL of meta-aramid solution into a film under the conditions of positive voltage +18 kV, negative voltage -6 kV, spinning speed 1 mL / h, spinning temperature 30°C, humidity 40%, and 23G needle;

[0074] Step 3, 0.21 g of 2-alkyl-methylimidazole, 20.92 g of brominated butyl rubber and 0.44 g of conductive carbon black are mixed with 78.43 g of tetrahydrofuran to prepare a conductive rubber latex;

[0075] Step 4: soak three layers of meta-aramid (5 cm×5 cm) in 10 mL of conductive rubber latex and dry them at a high temperature of 110° C. to obtain a flexible aramid-based triboelectric electrode material;

[0076] Step 5: Assemble the flexible aramid-based triboelectric electrode with polyvinylidene fluoride film, flexible copper tape, polyimide tape, polyethylene film and wire into a triboelectric nanogenerator, and then use a heating plastic sealing machine to plastic seal the polyethylene film. This will yield an aramid-based underwater triboelectric nanogenerator with high elasticity and high stacking power density.

[0077] In the above examples, the butyl imidazole system has the best mechanical properties because the butyl imidazole has the largest amount of cations per unit mass.

[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a flexible aramid-based triboelectric nanoelectrode material with high elasticity and high stacking power density, characterized in that: The specific steps include: Step 1, dissolving meta-aramid with an organic solvent to obtain a meta-aramid solution, and performing electrostatic spinning using the meta-aramid solution to obtain a meta-aramid nanofiber membrane; Step 2, blending an ionic liquid with a cationic group, brominated butyl rubber and conductive carbon black to prepare a conductive rubber latex; Step 3: stack multiple layers of meta-aramid and immerse them together in the conductive rubber latex obtained in the previous step, take them out and dry them at high temperature to obtain a flexible aramid-based triboelectric electrode material.

2. The method for preparing a flexible aramid-based triboelectric nanoelectrode material with high elasticity and high stacking power density according to claim 1, characterized in that: In the step 1, lithium bromide and N,N-dimethylacetamide are used to dissolve the meta-aramid, and the mass fractions of the meta-aramid, lithium bromide and N,N-dimethylacetamide are 8%, 10% and 82% respectively, and the dissolution temperature is between 60 and 90°C.

3. The method for preparing a flexible aramid-based triboelectric nanoelectrode material with high elasticity and high stacking power density according to claim 1, characterized in that: During electrospinning, the positive voltage of the electrospinning machine is +18kV, the negative voltage is -6kV, the spinning speed is between 1 and 1.5mL / h, the spinning temperature is greater than 15°C, the humidity is less than 50%, the spinning solution is not less than 5mL, and the needle model is: 23G.

4. The method for preparing a flexible aramid-based triboelectric nanoelectrode material with high elasticity and high stacking power density according to claim 1, characterized in that: In the step 3, the mass fractions of the cationic ionic liquid, brominated butyl rubber, conductive carbon black and tetrahydrofuran are 0.21%, 20.92%, 0.44% and 78.43% respectively.

5. The method for preparing a flexible aramid-based triboelectric nanoelectrode material with high elasticity and high stacking power density according to claim 1, characterized in that: The cation-carrying ionic liquid includes any one of butyl imidazole, 1-decyl-3-methyl imidazole tetrafluoroborate, 1-alkyl-2,3-dimethyl imidazole and 2-alkyl-methyl imidazole.

6. The method for preparing a flexible aramid-based triboelectric nanoelectrode material with high elasticity and high stacking power density according to claim 1, characterized in that: In the step 3, the number of layers of the meta-aramid film is three, the size is 5 cm×5 cm, the content of the conductive rubber latex is 5 to 25 mL, and the oven temperature is between 110 and 120° C.

7. Flexible aramid-based triboelectric nanoelectrode material with high elasticity and high stacking power density, characterized in that: Prepared by the method according to any one of claims 1 to 6.